A stochastic dairy transportation problem considering collection and delivery phases. (September 2019) - Huang, Kuancheng; Wu, Kun-Feng; Ardiansyah, Muhammad Nashir
Highlights: We formulate the integer programming models for the stochastic dairy transportation problem. We develop a heuristic algorithm based on the set-covering formulation. We perform the numerical experiment to affirm that the solution algorithm is helpful for the dairy cooperatives. Abstract: Based on the dairy cooperatives in Indonesia, this study formulates a stochastic programming model to handle the milk collection and delivery process with the maximum route duration limitation, the external cooling facility option, and travel time uncertainty. Besides, the local practice of sharing the fleet for both collection and delivery further complicates the decision. A set covering-based solution approach is used, due to its flexibility in handling complicated operational requirements and alignment with the decision environment. According to the numerical experiment, the proposed solution algorithm can provide quality solutions with a reasonable computational time for the cooperative operators.